Pediatric Program Leadership's Contribution Toward Resident Wellness - Carson, Savanna L.; Perkins, Kate; Reilly, Maura R.; Sim, Myung-Shin; Li, Su-Ting T. (Academic pediatrics, 2018)
Residency program leaders are required to support resident well-being, but often they do not receive training in how to do so. To determine frequency in which program leadership provides support for resident well-being, comfort in supporting resident well-being, and factors associated with need for additional training in supporting resident well-being. National cross-sectional web-based survey in June 2015 of pediatric program directors, associate program directors, and coordinators about their experiences supporting resident well-being. Univariate and bivariate descriptive statistics compared responses between groups. Generalized linear modeling, adjusting for program region, size, program leadership role, and number of years in role determined factors associated with need for additional training. The response rate was 39.3% (322/820). Most respondents strongly agreed that supporting resident well-being is an important part of their role, but few reported supporting resident well-being as part of their job description. Most reported supporting residents' clinical, personal, and health issues at least annually, and in some cases weekly, with 72% spending >10%of their time on resident well-being. Most program leaders desired more training. After adjusting for level of comfort in dealing with resident well-being issues, program leaders more frequently exposed to resident well-being issues were more likely to desire additional training (P < .02). Program leaders spend a significant amount of time supporting resident well-being. Although they think that supporting resident well-being is an important part of their job, opportunities exist for developing program leaders through including resident wellness on job descriptions and training program leaders how to support resident well-being.